2018
DOI: 10.1155/2018/7410246
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Outcomes of Extracorporeal Shock Wave Therapy in Early-Stage Femoral Head Osteonecrosis

Abstract: Objective Femoral head osteonecrosis is a progressive clinical condition with significant morbidity and long-term disability. Several treatment modalities including both surgical and nonsurgical options have been used with variable levels of success. High-energy extracorporeal shock wave therapy is a nonoperative treatment option that has been described for early-stage disease. We aimed to assess the functional and radiological outcomes of extracorporeal shockwave therapy (ESWT) in the treatment of osteonecros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
(39 reference statements)
0
23
0
Order By: Relevance
“…51 Nevertheless, an appreciable reduction in bone marrow edema from grades 3-4 to grades 1-2 was seen. 51 Long-term outcomes of shockwave therapy reported by Xie et al also demonstrated favorable outcomes among 39 patients with predominately stage II disease. 49 After the procedures, MRIs were taken during follow-ups at 6 months, 12 months, and then once a year.…”
Section: Alternative Therapiesmentioning
confidence: 91%
See 2 more Smart Citations
“…51 Nevertheless, an appreciable reduction in bone marrow edema from grades 3-4 to grades 1-2 was seen. 51 Long-term outcomes of shockwave therapy reported by Xie et al also demonstrated favorable outcomes among 39 patients with predominately stage II disease. 49 After the procedures, MRIs were taken during follow-ups at 6 months, 12 months, and then once a year.…”
Section: Alternative Therapiesmentioning
confidence: 91%
“…Patients were then followed up at 6 weeks and quarterly thereafter. 51 Algarni and Moallem observed substantial improvements in pain and HHS scores at 8 months, although MRI imaging demonstrated no statistically significant decrease in lesion size (p ¼ 0.23). 51 Nevertheless, an appreciable reduction in bone marrow edema from grades 3-4 to grades 1-2 was seen.…”
Section: Alternative Therapiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Over the past decades extracorporeal shock wave therapy (ESWT) has emerged as a promising treatment for many musculoskeletal conditions [14][15][16]. In particular, ESWT has shown therapeutic value for treating avascular necrosis of the femoral head [17][18][19][20] and osteochondral lesions of the talus [21].…”
Section: Introductionmentioning
confidence: 99%
“…Shockwaves are documented to stimulate bone regeneration, and it has been suggested that it may also induce specifi c signals for growth and maturation of the mesenchymal progenitors of the bone marrow. At the same time, shockwaves produce increased concentrations of free radicals [51][52][53][54][55] . A link has been detected between morphogenic proteins (BMP) and shockwave activity regarding bone regeneration.…”
Section: Introductionmentioning
confidence: 99%